2002
DOI: 10.1097/00002030-200211080-00010
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of adherence and viral load in a large multi-center cohort of HIV-infected women

Abstract: Antiretroviral adherence is not stable over time. Interventions aimed at monitoring and improving long-term adherence in women are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
177
2
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(197 citation statements)
references
References 23 publications
10
177
2
8
Order By: Relevance
“…26 Although reported barriers to adherence are consistent across multiple settings and countries, studies have also shown that adherence levels and the profile of factors that influence it differ by settings. [27][28][29] were allocated a number. Coupons bearing these numbers were put in a hat and randomly drawn to make the selection of the 10 to participate in the study.…”
Section: Introductionmentioning
confidence: 99%
“…26 Although reported barriers to adherence are consistent across multiple settings and countries, studies have also shown that adherence levels and the profile of factors that influence it differ by settings. [27][28][29] were allocated a number. Coupons bearing these numbers were put in a hat and randomly drawn to make the selection of the 10 to participate in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Paterson et al (2000) found that approximately 30% of patients were able to achieve this level, and Golin and colleagues (2002) found that only 4% of patients took 95% or more of their medications consistently. In addition, adherence rates tend to decline over time (Howard et al 2002;Ickovics et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The medication outcome typically most important to the clinician is a sustained period of adherence by the patient, but ample evidence documents considerable variability in antiretroviral adherence [28]. Well-designed prospective studies have highlighted the limitations of using baseline patient characteristics to predict adherence trajectories.…”
mentioning
confidence: 99%